High-flux hemodialysis combined with nutritional intervention: Effects on the nutritional status and clinical outcomes of patients with renal failure - Yang Liu; Rongrong Shen; Xuehua Pu; Yaqing Zhou; Binbin Zhang (PLoS ONE, 2026)
Background To evaluate the association between high-flux–based hemodialysis prescription combined with nutritional intervention and nutritional status and clinical outcomes in renal failure patients. Methods Patients admitted between January 2020 and August 2024 were divided into an observation group (high-flux hemodialysis, n = 115) and a control group (Conventional blood purification, n = 115). Renal function [β2-microglobulin (β2-MG), serum creatinine (Scr), blood urea nitrogen (BUN)], inflammatory markers [interleukin-6 (IL-6), C-reactive protein (CRP), tumor necrosis factor-α (TNF-α)], and nutritional indices [serum albumin (ALB), prealbumin (PA), transferrin (SF)] were compared. Cox multivariate analysis identified prognostic factors. Results Both groups exhibited post-treatment reductions in uremic markers (β2-MG: P < 0.05; Scr: P < 0.05; BUN: P < 0.05) and inflammation (IL-6: P < 0.05; CRP: P < 0.05; TNF-α:P < 0.05), with no baseline differences (P > 0.05). The observation group demonstrated significantly greater reductions in uremic markers and inflammatory markers versus controls (P < 0.05). Nutritional parameters (ALB, PA, SF) increased post-treatment in both groups (P < 0.05). Survival rates were higher in the observation group (P < 0.05). Deceased patients were predominantly≥60 years old, had cardiovascular comorbidities, and exhibited higher conventional blood purification utilization (P < 0.05).Lower ALB (P < 0.05) and elevated IL-6, CRP, TNF-α (P < 0.05) correlated with mortality.A reduced Cox model identified IL-6 (HR: 1.107, 95%CI: 1.063–1.153) and TNF-α (HR: 1.069, 95%CI: 1.012–1.130) as independent predictors of poor outcomes (P < 0.05). Conclusions High-flux-based hemodialysis prescription with nutritional support was associated with more effective clearance of uremic markers, improvements in nutritional status and inflammatory response, as well as better survival in renal failure patients. Elevated IL-6 and TNF-α levels were identified as significant predictors of mortality in the reduced Cox model.